2004
DOI: 10.1177/008124630403400409
|View full text |Cite
|
Sign up to set email alerts
|

Creating New Capacity through Postgraduate Selection

Abstract: The selection of students into professional training programmes in psychology has implica tions not only for the qua ¡ity of psychological services provided, but also for the psychological wellbeing of the South African population as a whole. This is reflective of broader social challenges related to questions of equity, redress and social justice. This article provides a critical evaluation of the extent to which institutions of higher learning in South Africa have, over the past 10 years, developed processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 6 publications
4
35
0
Order By: Relevance
“…This problem in not new, especially in relation to the presentation of psychologists in terms of race in South Africa. A report by Health Profession Council of South Africa (HPCSA) in 2002 indicated that 90% of the registered psychologists and therapists were whites, while 80% of registered intern psychologists were also whites (Foxcroft & Roodt, 2005;Mayekiso Strydom, Jithoo & Katz, 2004). The consequences of this over-representation of certain races in some careers include communication barriers and cultural insensitivity (Mayekiso et al, 2004).…”
Section: Adolescent Boys' Use Of Home Languages At the Child And Youtmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem in not new, especially in relation to the presentation of psychologists in terms of race in South Africa. A report by Health Profession Council of South Africa (HPCSA) in 2002 indicated that 90% of the registered psychologists and therapists were whites, while 80% of registered intern psychologists were also whites (Foxcroft & Roodt, 2005;Mayekiso Strydom, Jithoo & Katz, 2004). The consequences of this over-representation of certain races in some careers include communication barriers and cultural insensitivity (Mayekiso et al, 2004).…”
Section: Adolescent Boys' Use Of Home Languages At the Child And Youtmentioning
confidence: 99%
“…A report by Health Profession Council of South Africa (HPCSA) in 2002 indicated that 90% of the registered psychologists and therapists were whites, while 80% of registered intern psychologists were also whites (Foxcroft & Roodt, 2005;Mayekiso Strydom, Jithoo & Katz, 2004). The consequences of this over-representation of certain races in some careers include communication barriers and cultural insensitivity (Mayekiso et al, 2004). This threatens the level of engagement and communication between professionals and the children they are supposed to serve (Mayekiso et al, 2004;Robinson, 2001).…”
Section: Adolescent Boys' Use Of Home Languages At the Child And Youtmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey of 'race' distribution among 12 clinical psychology training programmes in South Africa across the period 1994, Mayekiso et al (2004 found that 'African' 1 students comprised between 25% and 31% of total student enrolments. Certainly, the years since the inception of democracy in South Africa have witnessed a progressive trend in the admission of 'Black' students into training programmes, spurred on by, inter alia, the stipulation by the HPCSA that 50% of all trainees should be 'Black' (Professional Board for Psychology, 2000).…”
Section: Clinical Psychology Training In South Africamentioning
confidence: 99%
“…Organised professional psychology has committed itself to working towards such change, and there is a growing literature on the experience of black trainees entering a formerly 'white' profession (Ahmed and Pillay 2004;Christian, Mokutu, and Rankoe 2002;Duncan, van Niekerk, and Townsend 2004;Mayekiso et al 2004;Nicholas 1993;Pillay 2003;Pillay and Kramers 2003;Pillay and Petersen 1996;Suffla, Stevens, and Seedat 2001;Swartz 1998). The road to transformation in professional psychology since the advent of democracy in 1994 has, however, not been as smooth as once might have been hoped (Mayekiso et al 2004), equity targets are not being fully met.…”
Section: Introductionmentioning
confidence: 99%